Strategi Bersaing Hotel Grand Rohan Jogja dalam Jasa Akomodasi Berbasis Syariah - Prayudi, Maximianus Agus; Wicaksono, Ajie (Jurnal Manajemen Bisnis dan Keuangan, 2022)
The purpose of this study is to analyze the implementation of sharia and the competitive strategy carried out by Grand Rohan Jogja, as well as efforts to overcome the various obstacles it faces. The research method uses a qualitative method of interviews which are analyzed using Miles and Huberman. The results obtained show that Hotel Grand Rohan Jogja applies principles and orientations that refer to the company's vision and mission and obtained halal certification from MUI on April 26, 2018. The competitive strategy of Hotel Grand Rohan Jogja prioritizes human resources and management by always improving performance, attitude, as well as sharia. Operations tailored to event predictions and room requests. Financial management with annual and monthly planning is prepared once a year, while marketing uses offline and online channels. Hotel Grand Rohan Jogja employees maintain friendliness and courtesy, promote offers that are not made by competitors, such as the All You Can Eat promo menu and spacious rooms for meetings/events, offer a varied menu of choices (western, Indonesian, Chinese food), 5 daily prayer calls, and Tahajud & Sahur Call. Grand Hotel Jogja also follows the government's policy, namely CHSE certification as a guarantee of security and comfort for visits and implementing health protocols.